Homology-directed repair in mouse cells increased by CasRx-mediated knockdown or co-expressing Kaposi's sarcoma-associated herpesvirus ORF52. Issue 10 (15th October 2019) - Pan, Hong; Yu, Weina; Zhang, Ming
Abstract: Precise genome editing with directed base insertion or targeted point mutations can be achieved by CRISPR/Cas9-mediated homology-directed repair (HDR) and is of great significance in clinical disease therapy. However, HDR efficiency, compared with non-homologous end-joining (NHEJ), is inherently low. To enhance HDR, enabling the insertion of precise genetic modifications, we compared two strategies during surrogate reporter assays in mouse N2A cells: the suppression of DNA ligase IV, a key molecule in NHEJ, using the CasRx ( Ruminococcus flavefaciens Cas13d) system, and co-expression of Kaposi's sarcoma-associated herpesvirus (KSHV) ORF52 proteins. We found that suppression of DNA ligase IV promotes HDR efficiency by 1.4-fold. When co-expressed with the Cas9 system, ORF52 improved HDR efficiency by up to 2.1-fold. In addition, we used ORF52 co-expression to modify the ACTB and Tubb3 genes of mouse N2A and E14 cells, which further increased HDR efficiency by approximately two- to four-fold. In conclusion, our data suggest that ORF52 co-expression is effective for enhancing CRISPR/Cas9-mediated HDR, which may be useful for future studies involving precise genome editing.